2009
DOI: 10.1002/jssc.200800565
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted polymer for the determination of trace ractopamine in pork using SPE followed by HPLC with fluorescence detection

Abstract: Original PaperMolecularly imprinted polymer for the determination of trace ractopamine in pork using SPE followed by HPLC with fluorescence detectionIn this study, a molecularly imprinted functionalized polymer for the selective separation of ractopamine (RAC) was prepared by combining a surface molecular imprinting technique with a sol -gel method process. The polymer was evaluated by static, kinetic adsorption, and selective experiments. Results indicated that the molecularly imprinted polymer had high adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Among these support particles, silica shows promising characteristics because it is a non-swelling inorganic material, stable under acidic conditions, and has high thermal resistance. Surface imprinting using silica as the support has been applied to imprint pharmaceuticals [37,38] and biological macromolecules [25,[39][40][41][42][43][44][45][46][47]. The structural analogues of the target molecules, namely the dummy templates, can avoid the leakage of the template of the analyte [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Among these support particles, silica shows promising characteristics because it is a non-swelling inorganic material, stable under acidic conditions, and has high thermal resistance. Surface imprinting using silica as the support has been applied to imprint pharmaceuticals [37,38] and biological macromolecules [25,[39][40][41][42][43][44][45][46][47]. The structural analogues of the target molecules, namely the dummy templates, can avoid the leakage of the template of the analyte [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…A pork sample was purchased from the local supermarket and determined to be free of RAC. The pretreatment procedure was according to the literature (Wang et al 2009a). A twenty-gram pork sample was weighed into a 100-mL polypropylene centrifuge tube, which was spiked with RAC at three levels 1, 1.5, 2.5 μg kg −1 , respectively.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…For this effect, RAC was introduced into the animal feed as feed additive for growth promotion instead of clenbuterol (the first generation of leanness-enhancing agent). It has been reported that RAC could significantly increase the lean meat percentage and improve the feed conversion ratio in pig and other farm animals (Kootstra et al 2005;Wang et al 2009a). Due to its extensive use, it was likely to cause RAC residues in edible animal products, such as muscle, kidney, or liver, which made it potentially hazardous to human health (Bergen et al 1989;Armstrong et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there was a progressive loss in MS signal intensity for the C18 extracts, due to a build-up of matrix on the ESI interface. Wang et al developed an on-line MIPs method for the selective isolation of ractopamine in pork [217].…”
Section: β-Agonistsmentioning
confidence: 99%